Important Role of Menarche in Development of Estrogen Receptor–Negative Breast Cancer in African American Women. (17th June 2015) - Ambrosone, Christine B.; Zirpoli, Gary; Hong, Chi-Chen; Yao, Song; Troester, Melissa A.; Bandera, Elisa V.; Schedin, Pepper; Bethea, Traci N.; Borges, Virginia; Park, Song-Yi; Chandra, Dhyan; Rosenberg, Lynn; et al.
Abstract : Background: Menarche is a critical time point for diverging fates of mammary cells of origin. African American women have young age at menarche, which could be associated with their high rates of estrogen receptor–negative (ER-) breast cancer. Methods: In the AMBER Consortium, using harmonized data from 4426 African American women with breast cancer and 17 474 controls, we used polytomous logistic regression to estimate odds ratios (ORs) and 95% confidence intervals (CIs) for ages at menarche and first live birth (FLB), and the interval between, in relation to ER+ and ER- breast cancer. All statistical tests were two-sided. Results: Risk of ER- breast cancer was reduced with later age at menarche among both parous and nulliparous women (≥15 vs <11 years OR = 0.62, 95% CI = 0.48 to 0.81 and OR = 0.56, 95% CI = 0.29 to 1.10, respectively), with no effect of age at FLB. For ER+ breast cancer, the inverse association was weaker among nulliparous women. While longer intervals between menarche and FLB were associated with increased risk of ER+ breast cancer in a dose-response fashion (OR for 20 year interval = 1.39, 95% CI = 1.08 to 1.79, P trend = .003), ER- risk was only increased for intervals up to 14 years and not beyond ( P trend = .33). Conclusions: While ER- breast cancer risk was markedly reduced in women with a late age at menarche, there was not a clear pattern of increased risk with longer interval between menarche and FLB, as was observed for ER+ breast cancer. These findings indicate that etiologic pathways involving adolescence and pregnancy may differ for ER- and ER+ breast cancer.